ANXIETY AND DEPRESSION IN DOCTORS UNDERGOING POSTGRADUATE TRAINING COURSES AT ARMED FORCES POSTGRADUATE MEDICAL INSTITUTE RAWALPINDI - Nisar, Kashif; Khan, Khalid Hayat; Shah, Mubashir (Journal of Ayub Medical College Abbottabad, 2012)
Background: In the recent past doctors own physical and mental health care has been a focus of research worldwide. The estimated suicide rate among doctors is approximately one per day. Various other studies reveal high scores of anxiety, depression, job dissatisfaction and burnouts. The study was carried out to determine the prevalence of anxiety and depression in doctors undergoing various postgraduate training courses at AFPGMI, Rawalpindi. Methods: This crosssectional study was carried out from June to December 2010 at Armed Forces Postgraduate Medical Institute, Rawalpindi. All willing available trainee doctors were included in the study. Urdu version of Beck's anxiety and depression scale was used. Results: Average anxiety score of all doctors was (8.05). The anxiety score was 15.7 in ENT, 12.0 in Pathology, 8.5 in Medicine, 7 in Basic Medical Sciences, 5.7 in Ophthalmology, 3.61 in Surgery, 3.3 in Radiology, and 3.05 in General Duty Medical Officers. With overall average score of (9.2), the average score on depression was highest in Anaesthesiology (20), followed by Radiology (10.05), Pathology (10.02), Basic Medical Sciences (9) Ophthalmology (8.2), Medicine (7), and General Duty Medical Officers (4.1). Conclusion: This study reveals an important area of doctors' own health which remains relatively neglected. Rectification measures are required to reduce anxiety/ depression, and mortality and morbidity among doctors. Keywords: Anxiety, Depression, Doctors, Morbidity